Comparative role of betalains and other key antioxidant metabolites in the photoprotection against acute exposure to UV-B radiation in Chenopodium quinoa and C. berlandieri seedlings - Causin, Humberto F.; Cá, Federico D.; Spotorno, Viviana Graciela; Palacios, María B.; Martínez Tosar, Leandro; Burrieza, Hernán F.; Tossi, Vanesa E. (Elsevier, 2025)
Chenopodium quinoa Willd. is a betalainic crop with remarkable tolerance to extreme environmental conditions. Despite numerous varieties grow at high altitudes, where UV-B radiation is intense, research on the effects of UV-B stress on this and related species is very scarce. In the present work we aimed to determine whether UV-B radiation induces the production of betalains, and evaluated the role of these pigments and other key antioxidants in preventing oxidative damage, in seedlings of C. quinoa (ecotypes CICA and Villarrica) and its close relative C. berlandieri Moq., grown in darkness and after exposure to an acute pulse of UV-B radiation (24 h, 2.5 W m−2). UV-B significantly increased MDA accumulation and induced the production of betalains (particularly betacyanins), polyphenols and UV-B-absorbing compounds in all seedlings tested. The activity of antioxidant enzymes showed comparatively minor changes, with the exception of GPOX which consistently decreased after UV-B irradiation. The degree of oxidative damage was not correlated to the concentration of betalains present in the tissues at the end of the treatment. However, when pigment synthesis was stimulated by short white light pulses prior to UV-B irradiation, the increase in MDA levels could be prevented in C. berlandieri seedlings despite no major changes occurred in most of the remaining metabolites evaluated, suggesting that betalains have an important role in controlling oxidative damage in this species. In contrast, the presence of high levels of polyphenolic compounds rather than the accumulation of betalains contributed to improved UV-B tolerance in C. quinoa seedlings.